The 5th horseman : a novel - Patterson, James, 1947- (Little, Brown and Co., 2006)
Healthy patients are dying of unknown causes in a San Francisco hospital and the Women's Murder Club decides to investigate the hospital's personnel. They discover a hospital administrator determined to shield the hospitals reputation.